2011
DOI: 10.1080/17538940903506006
|View full text |Cite
|
Sign up to set email alerts
|

Tracking desertification on the Mongolian steppe through NDVI and field-survey data

Abstract: Changing environmental and socio-economic conditions make land degradation, a major concern in Central and East Asia. Globally satellite imagery, particularly Normalized Difference Vegetation Index (NDVI) data, has proved an effective tool for monitoring land cover change. This study examines 33 grassland water points using vegetation field studies and remote sensing techniques to track desertification on the Mongolian plateau. Findings established a significant correlation between same-year field observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 43 publications
1
37
1
Order By: Relevance
“…Ground-truthing has shown the effectiveness of satellite assessment as an indicator of pasture conditions in the Gobi [36,42]. Prior fieldwork by the authors found NDVI results significantly correlated (p ≤ 0.01) with area vegetation line-transect data (basal coverage assessment, to 1-km) in the Gobi [43]. There are limitations in assessing a compact timespan in an arid landscape; however, this paper uses a longer temporal data set than employed in Tucker et al's [5] seminal work on desert areal extent.…”
Section: Methodsmentioning
confidence: 99%
“…Ground-truthing has shown the effectiveness of satellite assessment as an indicator of pasture conditions in the Gobi [36,42]. Prior fieldwork by the authors found NDVI results significantly correlated (p ≤ 0.01) with area vegetation line-transect data (basal coverage assessment, to 1-km) in the Gobi [43]. There are limitations in assessing a compact timespan in an arid landscape; however, this paper uses a longer temporal data set than employed in Tucker et al's [5] seminal work on desert areal extent.…”
Section: Methodsmentioning
confidence: 99%
“…It is difficult to set a standard threshold of vegetation coverage for different geographic landscapes and ecological characteristics, which is why we selected a series of thresholds in greenness in this research. In fact, regions of low greenness in this study are not limited to areas defined by desert in the "convention", but it can reflect the vegetation change of desert areas well [17][18][19][20]31]. In comparison with the fourth desertification survey of China, an NDVI value of less than 1500 can be used as an evaluation standard of desert.…”
Section: Determination Of An Index For Desertification Monitoringmentioning
confidence: 99%
“…Hot spots such as Inner Mongolia, Horqin grassland, Hulunbuir, Ordos, Qinghai-Tibet Plateau, Minqin, and the three north shelter forests, are major focal areas of previous remote sensing research [9][10][11][12][13][14][15][16][17][18][19][20][21][22], and there is no desertification analysis about the whole territory of China. Time series data used in existing research are mostly before 2000, incomplete since 2000 to nowadays [9][10][11][12][13][14][15][16][17][18][19][20][21][22], and there is still no report for the time period of 2000 and 2010. Therefore, in this paper we aim to map China's desertification between 2000 and 2010 based on international standard and definition of desertification, and the capability of remote sensing technology, in order to lay a foundation for China's long-term remote sensing monitoring of desertification.…”
mentioning
confidence: 99%
“…The conservation analysis was made according to the method proposed by Meini et al [2013a,b] in using a vegetation index into a sample area of the sheep track. Since its wide use with very good results in remote sensing researches [see e.g., Iamonico, 2008;Sternberg et al, 2010;Duringon et al 2012;Alphan and Derse, 2013;Schucknecht et al, 2013] the Normalized Difference Vegetation Index (NDVI) was chosen. It is a standardized index which generates an image displaying greenness (relative biomass).…”
Section: Methodsmentioning
confidence: 99%